Aspekty ryzyka w usłudze faktoringu z perspektywy banku - Gwiazda, Mariusz (Risk in the Factoring. The Banks Perspective, 2006)
Dynamic growth of factoring services in Poland can be observed in the last few years. The volume of this transaction is still increasing as well as a number of the subjects which offer them. The main aim of this article is to show these aspects of the risk which, from the bank's point of view, concern the factoring but are not the typical kinds of the risk for other credit products. This report does not concern the issue of usual credit risk (active and passive) but shows the selected kinds of the risk and presents their detailed analysis. The main attention is given to the merchant's credit authenticity problem which has a very important meaning in the factoring service.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (5); 2006; nr 1120, s. 61-73